Digitization of archive material in Military archives - Pavlović, Rade Mirko (Vojnotehnički glasnik / Military Technical Courier, 2013)
This work decribes the Archive Digitization Application – ADA. The application was made on the request of the Military Archives of the Ministry of Defence of the Republic of Serbia and follows the complete structure of archives organization. The most important parts of the application for digitization of documents have been described as well as tasks of work posts for digitization of documents. The process of digitization can be divided into three phases in order to protect documents and to present them in the most efficient way to users – researchers. Though a term ’scanning’ is commonly used, digitization is a complex process and requires realization of all phases in order to get the final product. At the same time, an increased possibility of access to a larger number of documents is given to researchers with no dependancy on available resourses in terms of bringing out and returning archival material from and to archives depots. This work also presents the visual appearance of the application for  some parts of the digitization process.. Introduction Problems of archives can be classified into two groups.The first group of problems concerns deterioration of archive material and its protection, while the second group represents engagement of a large number of personnel involved in working with researchers of archival material for different purposes. Both groups of problems can be solved, for the most part, by archive material digitization. The parts of the funds in paper or other analog forms which are in bad condition would be thus preserved; furthermore, it would enable access to documents to a larger number of researchers with less engagement of personnel. Archive material digitization is a complex process and consists of several phases in order to get the final product, a digitized document which can be accessed in the easiest possible way. Each of the phases must be well planned in order to carry out the process effectively. Therefore, in order to meet the needs of the Military Archvies of the Ministry of Defence of the Republic of Serbia, the ADA (Archive Digitization Application) program has been made to follow the process of digitization and make work easier and faster. Digitization Application The phases of the digitization process and the ADA program are production, working with users (researchers) and access to digitized documents. The Application defines several access levels and each of the program users logs on with their username and password. During login, only the parts of the program of interest to a certain type of user are opened. Production, as one of the phases of digitization, includes several sub-units, such as scanning, entry of short contents of documents and control. The ADA application was made in such a way that through automatization it enables a more efficient realization of scanning and content entry as the most time-consuming phases. After the completion of scanning and content entry, the result is a digital document that undergoes control before being delivered to researchers for examination. There are two kinds of control, subjective and computer control. Subjective control envisages the examination of each document by a supervisor – controller and comparison with the original analog document, while in the case of computer control the signature of the scanned document is compared with the signature of short contents and they are thus connected. Also, the Application provides the possibility of OCR for more recent documents which are readable for these types of software. Working with researchers envisages a number of actions for the purpose of determining the correct approach to interested researchers and monitoring the researchers’ work. Researchers are issued research permits in the form of chip cards, with which they log on to the Application. In the process, the level of access and the period of validity of the issued permits is determined. The Application enables the administrator to check active researchers and the type of archive material they researched in the past period. Access can be achieved to all documents a researcher has opened and set aside for recording to one of the media and for printing. Also, it is possible to change the permit type and its validity, i.e. the extension of validity and termination. Accessing digitized archive material is very simple and efficient. Digitized archive material is accessed through a Web browser, with login by a chip card. The documents can be accessed in two ways: through the Military Archive structure and through a keyword. The former is used much more as it is more reliable than the keyword search which only takes into account the information added from the short contents, but for a quick search one can also use this kind of research. When examining digitized documents, researchers fill out a form if they are interested in obtaining a copy of a certain document, and the information on the requested document is forwarded to the administrator. Conclusion The best characteristics  of the ADA application are confirmed by previous use in the process of digitization of the archive material of the Military Archives. The amount of more than 4 million sheets of archive material efficiently digitized and accessible to researchers presents this Application as a good solution for digitization of archives and its use in other similar systems.
Keywords: digitization application; digital document; digitization